“Segunda evaluación del efecto entre el cultivo asociado de yuca (manihot esculenta grantz) con caupí (vigna unguiculata L. walp) en un suelo del Bajo Mayo” - Satalaya Reátegui, Haroldo (1997)
In the present work, the country phase has been developed, from 05-02-94 to 07-09-94 ih the Banda de Shilcayo district, province and San Martin Region. It has preved a second evaluation of effets between the associated yuca growing (Manihot Sculents Crants) with in a place in the Bajo Mayo; using five (05) treatments in study¡ three of them are considerated the witness, using t.he "Ar··pón F:umo" variety fer the yuca and "San Roque" fcw the Ci:itUj:ii • The treatments in study are T-1 (Yuca salo in a simple line sowed to 1.00 m x 1.00 m); T-2 (Caupi salo sowed to 1.80 m 0.60 m x 0.60 m)¡ T-3 (Yuca only in a double line (0.60 m x 0.60 m); T-4 (Yuca in a doble line more two lines of caupi~ sowed to 1.80 m x 0,60 m x 0,60 m the Yuca and to 0.25 m x It is demostrated that the sowing of in a double line in reserved roots so T-3 demostrate a yield of 25177,57 Kg/Ha, T-4 26190,43 Kg/Ha, T-5 26223,93 Kg/Ha. The Yuca caupi association has a better table of contents equal to the land (IET) in comparison with its respective monoculture, as a result of a better progress of using the land. It iE. r-~z·C